1997
DOI: 10.1111/j.1399-3038.1997.tb00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of soy allergy and/or intolerance in children, and clinical use of soy‐protein formulas

Abstract: Atopic diseases of infants and children are common, debilitating, chronic and sometimes even life-threatening. Several well-conducted studies in high risk babies have demonstrated a significant reduction in the prevalence and severity of atopic diseases with dietary and environmental manipulations. The currently available cow's milk (CM) substitutes for infants are soy protein (SP) formulas (SPFs), hydrolyzed formulas (HF), and home-made meat-based formulas. Soybeans have been cultivated in Eastern countries f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 99 publications
1
32
0
2
Order By: Relevance
“…Some studies have shown that feeding SPFs for the first six months of life significantly reduces the prevalence of atopic diseases in high risk babies. Several studies have confirmed the preventive effect of breastfeeding supplemented with SPFs [1][2][3] but others did not confirm this assumption [4,5].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Some studies have shown that feeding SPFs for the first six months of life significantly reduces the prevalence of atopic diseases in high risk babies. Several studies have confirmed the preventive effect of breastfeeding supplemented with SPFs [1][2][3] but others did not confirm this assumption [4,5].…”
Section: Introductionmentioning
confidence: 97%
“…We have reviewed eight pertinent studies [1] and found a mean of 20% of reactions, also considering two studies limited to 9 or 10 children and one that found a 0% prevalence [1,28]. This also means that 80-100% of infants and children with gastrointestinal disorders can ingest SPFs with impunity.…”
Section: Antigenicity or Allergenicity Of Spf?mentioning
confidence: 99%
See 2 more Smart Citations
“…As regards the allergenicity of soy, we have studied 143 children with a median age of 12 months affected by AD, who had been soy-protein-formula fed for at least three months [51]. Only 4/36 children with positive RAST to soy had a positive challenge test to soy.…”
Section: The Role Of Food Allergensmentioning
confidence: 99%